Effects of Intensive Control of Glycemia on Clinical Kidney Outcomes in Type 2 Diabetes Patients Compared with Standard Control: A Meta-Analysis - Herrera-Gómez, Francisco; Asensio-González, María; González-López, Anunciación; Álvarez, F. Javier (Frontiers in Pharmacology, 2017)
Background. Association between poor control of glycemia and the onset of microvascular complications in type 2 diabetes mellitus (T2DM) patients is a hard issue. However, it seems that the impact of pharmacological treatment is important only in early stages of diabetic nephropathy. We sought to examine whether intensive glycemic control is associated with improvement of clinical Chronic Kidney Disease (CKD) outcomes compared to standard glycemic control. Methods. Meta-analysis of published and unpublished randomized controlled trials (RCT) and post-hoc analysis of RCTs comparing anti-diabetic drugs and/or insulin (intensive control) versus dietary measures (standard control) for relevant outcomes related to progression of CKD clinically manifest was undertaken. Summary estimates obtained by random effects model and funnel plots for assessing reporting bias are presented. Results. Our analysis was based on 4 RCTs representing 27391 adult T2DM patients with CKD from around the world. The pooled OR for the outcomes of doubling of serum creatinine and need of dialysis were, respectively, of 0.98 with 95% confidence interval (95% CI) 0.81 to 1.19, and 0.84 with 95% CI 0.69 to 1.02. The pooled OR for the outcome of death from kidney failure was 0.62 with 95% CI 0.39 to 0.98. Clinical differences between studies were not translated in statistical heterogeneity. Reporting bias may be present. Conclusions. Intensive glycemic control has an effect on death from kidney failure compared to standard glycemic control. Better comprehension of glycemic control effects on both T2DM patients with and without CKD is important for individualization of these two treatment modalities.